The Effectiveness of Quiz and Vocab Arabic Based on Android Applications as Mutholaah Mufrodat Arabic Class VIII - Faizzaturahmah*, Faizzaturahmah; Abidin, Zaenal (Universitas Syiah Kuala, 2023)
One of the attempts to solve the problem of learning the Arabic language is through improving understanding of vocabulary using learning media, one of which is reading. The teaching aids varied, depending on how the teacher used them. This study aims to find out the effectiveness of vocabulary reading with Arabic QV application to improve the ability to memorize Arabic vocabulary for eighth grade B students in MTSN 1 Surakarta. The research approach used is quantitative with a type of associative quantitative. This study used pre-test and post-test. The study used a saturated sample method with a sample of 20 student. Data collection method using observation, questionnaires and testing. The data analysis techniques used in this study are samples related t-test and the N-Gain test or the previously conducted efficacy test, the precondition test which is the normality test. The result showed that there were significant differences of the vocabulary studied before and after using the vocabulary studied with the Arabic QV app that was appearing from the average pre-test value of the test question 70, while the average post-test score was 80. Then he conducted a different test using the formula t test the relevant sample, which is the sig value. (2-tailed) of 0.000 which means less than 0.05 then H0 is rejected and HA is accepted which means that there is a difference in the values before the test and after the test on the Arabic vocabulary studied by the students after applying the vocabulary reading with the QV applied Arabic. Muthanna vocabulary with Arabic QV application is effective for improving the ability to memorize Arabic vocabulary for eighth grade B students in MTSN 1 Surakarta shows results using an N-Gain test formula of 32 which means it has a potency level in the moderate category. So that the vocabulary can be completed and read with an effective Arabic QV application to improve the ability to memorize Arabic vocabulary of eighth grade B students in MTSN 1 Surakarta